The Implementation of Standards of Educators and Education Personnel in SMP Negeri 1 Sungai Raya Kubu Raya Regency - Lamazi Lamazi; Maswardi M. Amin; M. Chiar (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to obtain comprehensive information on the Implementation of Standards of Educators and Education Personnel in SMP Negeri 1 Sungai Raya Kubu Raya Regency related to How the Standards of Educators and Education Personnel and any factors that inhibit and support in implementing it and what efforts are made by the Headmaster in implementing the Standards of Educators and Education Personnel in SMP Negeri 1 Sungai Raya Kubu Raya Regency. This research is descriptive qualitative research. The data source consists of Headmaster, Educators and Education Personnel. The data collection procedure is done by observation, structured and in-depth interviews, and documentation. Validity checking the results is performed by member check, reference sufficiency, and triangulation. Data analysis used is a qualitative analysis that is by describing and interpreting data. The result of the conclusion is as follows: (1) Work Program of Educator Standard and Education Personnel at SMP Negeri 1 Sungai Raya Kubu Raya Regency has been running well, (2) Education Standard and Education Personnel in SMP Negeri 1 Sungai Raya Kubu Raya Regency also very good, because in terms of applying these standards the Headmaster does not have difficulties, as all school personnel have an awareness of their duties and responsibilities. (3) Communications conducted in implementing the Standards of Educators and Education Personnel in SMP Negeri 1 Sungai Raya Kubu Raya Regency is also well underway. (4) The supporting factors faced by the Headmaster in implementing the Standards of Educators and Education Personnel at SMP Negeri 1 Sungai Raya Kubu Raya Regency are all Educators and Education Personnel meet the Educational qualifications required by the Government and the educator has been certified. The inhibiting factor is lack of library personnel who specifically manage the library and laboratory professionals in their field. How to overcome these obstacles is the Headmaster provides an additional duty to the teacher to become head of the library and the laboratory, meanwhile for library staff and laboratory personnel the school assigns the honorarium. (5) The Headmaster’s efforts in implementing the Standards of Educators and Education Personnel at SMP Negeri 1 Sungai Raya of Kubu Raya Regency is by involving them in the preparation of the RKAS, establishing TPS and TPK, IHT, actively encouraging in the MGMP. Educators and Education Personnel improve their academic qualification and competency standards through various activities, including further studies, partnerships with other schools, programmed discussions, etc. The competence owned Educator, of course, affects the learning process and improving the quality of learners learn.